Pre-diagnostic plasma concentrations of Fibrinogen, sGPIIb/IIIa, sP-selectin, sThrombomodulin, Thrombopoietin in relation to cancer risk: Findings from a large prospective study - Graf, Mirja E.; Johnson, Theron S.; Schübel, Ruth; Katzke, Verena; Bugert, Peter; Hoffmeister, Michael; Kaaks, Rudolf; Kühn, Tilman (International journal of cancer, 2018)
While enhanced platelet activation may drive cancer progression and metastases, less is known about its role in early cancer development. Thus, we evaluated whether pre-diagnostic biomarkers of platelet activation and coagulation are related to the risks of common cancers in the prospective EPIC-Heidelberg Study using a case-cohort design. Levels of fibrinogen, soluble glycoprotein (sGP) IIb/IIIa, soluble P-selectin (sP-selectin), soluble thrombomodulin (sTM), and thrombopoietin (TPO) were measured in baseline plasma samples of a random subcohort (n = 2,480) and incident cases of breast (n = 605), prostate (n = 543), and colorectal cancer (n = 249). Multivariable Cox regression models revealed no statistically significant associations between biomarker concentrations and any of the cancer endpoints. Subgroup analyses showed a significant inverse relationship between TPO and colorectal cancer among men, with a hazard ratio (HR, highest vs. lowest quartile) of 0.60 (95% confidence interval: 0.37,0.95), whereas no significant association was observed among women. With regard to fibrinogen levels and breast cancer risk, there was a significant positive association among nulliparous women (HR: 2.53 [95% CI: 1.21, 5.30]), but not among parous women. Overall, our data suggest that enhanced platelet activation and a pro-coagulative state may not be related to increased risks of common cancers, although studies on other potential biomarkers of platelet activation and further cancer types are needed. Findings from our subgroup analyses require further investigation, as potential underlying mechanisms are not known.